Konsep Manajemen Kesiswaan di SMP Islam Terpadu Al Kahfi Bogor - Asep Sugandi (Program Studi Magister Pendidikan Agama Islam, 2022)
This study aims to convey the patterns or concepts and core models of student management applied at the Al Kahfi Islamic Middle School in Bogor, West Java. This study used qualitative research methods. Supporting data is done through interviews, direct research, and literature study. In this writing, the main subject of the information is the principal, deputy director of research programs, and deputy director of student affairs, as well as several students and subject teachers as well as some school administrative staff. From this research, it can be seen that the student management process is in accordance with the goals of the school, the mechanism for admitting new students is in accordance with a very strict selection procedure with the stages of writing tests for basic mathematics, Indonesian, PAI and reading and writing tests of the Alquran, there is student coaching. and counseling services as a place to guide students to have good morals or character, monitoring student activities carried out by the head and school representatives in the field of student affairs every week.AbstrakPenelitian ini bertujuan untuk menyampaikan tentang pola atau konsep dan model inti manajemen peserta didik yang diterapkan di SMP Islam Terpadu Al Kahfi Bogor, Jawa Barat. Penelitian ini menggunakan metode penelitian kualitatif. Data pendukung dilakukan melalui interview, penelitian langsung, dan studi pustaka. Dalam penulisan ini, subjek utama informasi adalah kepala sekolah, wakil direktur program penelitian dan wakil direktur kesiswaan, serta beberapa siswa dan guru mata pelajaran serta beberapa staf administrasi sekolah. Dari penelitian ini dapat diketahui bahwa proses proses manajemen kesiswaan sesuai dengan tujuan dari sekolah, mekanisme penerimaan siswa baru di sesuai dengan prosedur seleksi sangat ketat dengan tahapan tes tulis pelajaran matematika dasar, bahasa Indonesia, PAI serta tes baca tulis Al-Quran, terdapat pembinaan siswa dan layanan konseling sebagai tempat untuk membimbing siswa agar mempunyai akhlak atau karakter yang baik, monitoring kegiatan kesiswaan yang dilakukan kepala dan wakil sekolah bidang kesiswaan di setiap minggunya.